Análisis de las reformas tributarias referentes a las sanciones pecuniarias aplicadas por el servicio de rentas internas a los contribuyentes denominados: personas naturales obligadas y no obligadas a llevar contabilidad de la ciudad de Quito y su impacto durante el periodo 2008-2012 - Benalcázar Lagos, Estefanía Elizabeth (2014)
During the period 2008-2012 , the Tax Administration has been on the need for stricter financial penalties as a mechanism to prevent and punish the delay or omission of the tax returns , as well as , the commission of offenses and regulatory offenses , because to persisting problems of tax evasion and avoidance . This is why it is essential to determine the causes of these problems and their impact on the economy of individuals required and not required to keep accounting.